In partnership, for partnership: An international conference on humanitarian action (Special section editorial) - Ungras, Oshish; Brockett, Gavin (International Journal for Students as Partners, 2024)
After almost a year of planning an international conference on student partnership for humanitarian action with the UN Refugee Agency, a student-faculty partnership reflect on the learning process they undertook, and how years of working together built a strong foundation for this project. Working in partnership to communicate the importance of partnership to address complex global issues signifies the importance of engaging multi-level stakeholders in new, innovative solutions. This introduction to the special section titled after the conference provides the context for this challenging yet rewarding feat made possible with a community of partnerships.